2014
DOI: 10.1093/bfgp/elu016
|View full text |Cite
|
Sign up to set email alerts
|

Structural variations in plant genomes

Abstract: Differences between plant genomes range from single nucleotide polymorphisms to large-scale duplications, deletions and rearrangements. The large polymorphisms are termed structural variants (SVs). SVs have received significant attention in human genetics and were found to be responsible for various chronic diseases. However, little effort has been directed towards understanding the role of SVs in plants. Many recent advances in plant genetics have resulted from improvements in high-resolution technologies for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
166
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(171 citation statements)
references
References 86 publications
4
166
0
1
Order By: Relevance
“…However, genome wide patterns of structural variation in plant genomes are difficult to assess 27 , and previous efforts have relied on short read mapping, which misses the vast majority of intergenic spaces where most rearrangements are likely to occur 10 . To investigate structural variation at a genome wide scale, we generated optical maps (Extended Data Table 1) for two additional maize inbred lines: the tropical line Ki11, one of the founders of the maize nested association mapping (NAM) population 28 , and W22, which has served as a foundation for studies of maize genetics 29 .…”
Section: Openmentioning
confidence: 99%
“…However, genome wide patterns of structural variation in plant genomes are difficult to assess 27 , and previous efforts have relied on short read mapping, which misses the vast majority of intergenic spaces where most rearrangements are likely to occur 10 . To investigate structural variation at a genome wide scale, we generated optical maps (Extended Data Table 1) for two additional maize inbred lines: the tropical line Ki11, one of the founders of the maize nested association mapping (NAM) population 28 , and W22, which has served as a foundation for studies of maize genetics 29 .…”
Section: Openmentioning
confidence: 99%
“…In Arabidopsis, SV deletions were found to affect more than 2000 protein coding genes (Cao et al, 2011), and in maize, SVs were found to be enriched at loci associated with important agronomical traits including leaf development and disease resistance (Chia et al, 2012). Despite these findings, the formation mechanisms of plant SVs and their functional impact still remain largely unexplored (Saxena et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…of PAVs proves their connection with ancestral evolution and domestication [34]. PAVs are also found in mitochondrial DNA of maize [2,33]. CIMMYT, China and Brazil [21].…”
mentioning
confidence: 80%